Identification of Clausine E as an inhibitor of fat mass and obesity‐associated protein (FTO) demethylase activity. Issue 10 (19th July 2019) - Wang, Ying; Li, Junya; Han, Xinxin; Wang, Ning; Song, Chuanjun; Wang, Ruiyong; Chang, Junbiao
Abstract: The alkaloids containing a carbazole nucleus are an established class of natural products with wide range of biological activities. A combination of thermodynamic and enzymatic activity studies provides an insight into the recognition of Clausine E by the fat mass and obesity‐associated protein (FTO). The binding of Clausine E to FTO was driven by positive entropy and negative enthalpy changes. Results also indicated that the hydroxyl group was crucial for the binding of small molecules with FTO. The structural and thermodynamic information provides the basis for the design of more effective inhibitors for FTO demethylase activity. Abstract : The characteristics of the binding between Clausine E and the fat mass and obesity‐associated protein were investigated by physicochemical and spectroscopic techniques.